Downward nominal wage rigidity in services: direct evidence from a firm survey - Daniel Radowski; Holger Bonin (Institute for the Study of Labor (IZA), 2009)
The paper uses a new German employer survey on wage setting practices to analyze incidence and sources of nominal wage rigidity in services vs. manufacturing. We observe that wage freezes are significantly more frequent and wage cuts less frequent in services. Reasons preventing wage cuts reported by employers suggest that fear of excess worker turnover could explain this distinct behavior.
urn:nbn:de:101:1-20090119193
Keywords: J31; 330; Nominal wage rigidity; efficiency wages; manufacturing and services; Germany; Lohnrigidität; Effizienzlohn; Dienstleistungssektor; Verarbeitendes Gewerbe; Vergleich; Arbeitsmobilität; Deutschland